Brief report: noise reduction in preschool from a self-regulated learning perspective—implementation of a game-based voice regulation training program - Sarfaty, Lihi; Ben-Eliyahu, Adar (Frontiers in Psychology, 2023)
An 8-week voice regulation training program (VRTP) incorporating everyday activities was implemented in an experimental preschool classroom (EG; n = 34), which was compared with a control preschool classroom (CG; n = 31). The VRTP includes songs, games, and conversations aiming to raise children's awareness of noise levels and teach voice modulation skills. Grounded in the theoretical framework of self-regulated learning, the study's objectives were to evaluate the impact of the VRTP on noise levels, children's self-regulation, and pre-literacy skills. Noise levels were assessed weekly using an electronic noise meter before and during the program. The EG preschoolers demonstrated modest but significant improvements over their pre-VRTP levels of voice modulation, behavioral and emotional self-regulated learning, and pre-literacy skills, in contrast with the CG children. The findings provide evidence that young children's self-regulation may be enhanced in preschool, challenging the field of developmental–educational psychology to consider self-regulated learning during early childhood.